Applying Scenarios in the context of Specific User Design: Surgeon as an Expert User, and Design for Handicapped Children. - Thomann, G.; Rasoulifar, R.; Villeneuve, F. (Cranfield University Press, 2009)
In the context of specific user (surgery or handicap domain), the list of requirements is especially difficult to establish. We propose to reflect on the design methodology and especially on the Scenario & Emulation application. The aim is to make emerge needs in users who have specific relation to the final product. In this paper, we illustrate the research with two projects: the DESTIN Project (know-how and experience of the surgeons) and the AE2M Project (handicapped children). User, usage and products are the parameters we chose to define and to categorize with the objective to optimise the design process.
Organised by: Cranfield University
Keywords: Emulation & Scenario; User Centred Design; Design Methodology; Handicapped children; Design in Surgery; Specific User